Che‐1 is targeted by c‐Myc to sustain proliferation in pre‐B‐cell acute lymphoblastic leukemia. (24th January 2018) - Folgiero, Valentina; Sorino, Cristina; Pallocca, Matteo; De Nicola, Francesca; Goeman, Frauke; Bertaina, Valentina; Strocchio, Luisa; Romania, Paolo; Pitisci, Angela; Iezzi, Simona; Catena, Valeria; Bruno, Tiziana; et al.
Abstract: Despite progress in treating B‐cell precursor acute lymphoblastic leukemia (BCP‐ALL), disease recurrence remains the main cause of treatment failure. New strategies to improve therapeutic outcomes are needed, particularly in high‐risk relapsed patients. Che‐1/AATF (Che‐1) is an RNA polymerase II‐binding protein involved in proliferation and tumor survival, but its role in hematological malignancies has not been clarified. Here, we show that Che‐1 is overexpressed in pediatric BCP‐ALL during disease onset and at relapse, and that its depletion inhibits the proliferation of BCP‐ALL cells. Furthermore, we report that c‐Myc regulates Che‐1 expression by direct binding to its promoter and describe a strict correlation between Che‐1 expression and c‐Myc expression. RNA‐seq analyses upon Che‐1 or c‐Myc depletion reveal a strong overlap of the respective controlled pathways. Genomewide ChIP‐seq experiments suggest that Che‐1 acts as a downstream effector of c‐Myc. These results identify the pivotal role of Che‐1 in the control of BCP‐ALL proliferation and present the protein as a possible therapeutic target in children with relapsed BCP‐ALL. Synopsis: The RNA polymerase II‐binding protein Che‐1 is highly expressed at the onset of pediatric BCP‐ALL, but is down‐regulated with c‐Myc during remission. Che‐1 sustains c‐Myc‐dependent blast cells by directly regulating an overlapping set of cell proliferation genes. Che‐1/AATF is highly expressed in pediatric B‐cell precursor acute lymphoblastic leukaemia (BCP‐ALL). Che‐1 expression is regulated by the oncogene c‐Myc. Che‐1 is required for BCP‐ALL proliferation. Che‐1 and c‐Myc control similar pathways, suggesting that Che‐1 is a downstream effector of c‐Myc. Abstract : The RNA polymerase II‐binding protein Che‐1 is highly expressed at the onset of pediatric BCP‐ALL, but is down‐regulated with c‐Myc during remission. Che‐1 sustains c‐Myc‐dependent blast cells by directly regulating an overlapping set of cell proliferation genes.